PATTERN OF SELF MEDICATION AND DRUGS USE BEHAVIOR AMONG UNDERGRADUATE STUDENTS OF MEDICAL AND NON MEDICAL COLLEGES IN A CITY OF NORTH EAST INDIA- A COMPARATIVE STUDY - Dutta, Sarmistha; HAZARIKA, KAPIL (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective- The present study was undertakenÂ Â to assess and compareÂ the practiceÂ of self medication and drug use behaviorÂ amongÂ undergraduate students of medical and non-medical colleges in a city in North-EastÂ India. Method- A cross sectional questionnaire based study was conducted among 300 undergraduate students each of medical and non medical colleges ofÂ Guwahati city of Assam after taking informed consent . Approval ofÂ InstitutionalÂ Ethical Committee was taken prior to the commencement of the study. Data was collected with a prevalidated questionnaire related to various aspects like class of drugs used for self medication, conditions for which self medication may be employed and their knowledge, attitude and practice of self medication etc. Statistical analysis Â of the data was done. Result- In our study,71% of medical students and 63% of non medical students practiced self medication which was statistically significant. The most common drugs for self medicationÂ were analgesics and anti pyretics. Both medical and non medical students considered non severity of illnesses and quick relief from symptoms as the major reasons for self medication. The major information source for most of medical studentsÂ who practiced self-medication were textbooks and package inserts. Medical students prefer Allopathic system of medicine and Non medical students are more inclined towards Ayurvedic system. Conclusion- Practice, Knowledge and Awareness about self medication is significantly more in medical students in comparison to non medical students which can be attributed to their medical knowledge. Keywords- Self medication, Questionnaire, Package inserts, Allopathic, Awareness, Â Pharmacy. Â